2022
DOI: 10.1111/bcp.15582
|View full text |Cite
|
Sign up to set email alerts
|

Trends in oral anticoagulant use in patients with atrial fibrillation in Belgium from 2013 to 2019: A nationwide cohort study

Abstract: Non-vitamin K antagonist oral anticoagulants (NOACs) are increasingly preferred over vitamin K antagonists (VKAs) in atrial fibrillation (AF) management. However, differences in oral anticoagulant (OAC) prescribing according to patient's age, sex and physician's specialty may be present. Therefore, incident and prevalent use of OACs, NOACs and VKAs, stratified by age, sex and prescriber, and factors associated with the choice of OAC were investigated. Methods: Using two Belgian nationwide healthcare databases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Details on the study methodology have been published before and are provided in the Supplementary Materials (available in the online version) . 13,20 In brief, two nationwide databases provided the source population, namely the InterMutualistic Agency (IMA) database and Minimal Hospital Dataset (MHD).…”
Section: Methods Source Populationmentioning
confidence: 99%
“…Details on the study methodology have been published before and are provided in the Supplementary Materials (available in the online version) . 13,20 In brief, two nationwide databases provided the source population, namely the InterMutualistic Agency (IMA) database and Minimal Hospital Dataset (MHD).…”
Section: Methods Source Populationmentioning
confidence: 99%
“…Details on the study methodology have been published before and are provided in the supplemental materials [ 17 , 25 ]. In brief, two nationwide databases provided the source population, namely the InterMutualistic Agency (IMA) database and Minimal Hospital Dataset (MHD).…”
Section: Methodsmentioning
confidence: 99%
“…From 1 January 2013 to 1 January 2019, persons aged ≥45 years old and with ≥1 year coverage by a health insurance fund were included from the IMA database on the first date of filling an OAC prescription (=index date) ( Figure S1 ). NOAC users, namely dabigatran (approved in Belgium since August 2012), rivaroxaban (approved since September 2012), apixaban (approved since September 2013) and edoxaban (approved since October 2016), and VKA users (warfarin, acenocoumarol, phenprocoumon) were included [ 17 ]. Only OAC-naïve subjects were considered, excluding OAC-experienced subjects with an OAC prescription filled ≤1 year before the index date.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details on the study methodology have been reported before [7] , [19] , [20] . In brief, two nationwide databases, the InterMutualistic Agency (IMA) database and Minimal Hospital Dataset (MHD), provided the source population.…”
Section: Methodsmentioning
confidence: 99%